The Success Rate of Non-Penetrative Pre-Slaughter Stunning on Australian Brahman Cross Cattle Slaughter in Indonesia - Supratikno; Setijanto, Heru; Nuraini , Henny; Nurhidayat; Agungpriyono, Srihadi; Sudarnika, Etih; Nisa’, Chairun; Novelina, Savitri; Dwi Cahyadi, Danang (Acta VETERINARIA Indonesiana, 2024)
This study was conducted to evaluate the success rate of non-penetrative pre slaughter stunning (NPPSS) and the factors that influence it in 460 Australian Brahman cross cattle. Observations were made on the handling of cattle, the implementation of NPPSS, the slaughtering process until the animal was declared dead. The results showed that the stunning success rate of NPPSS (SSR) was 74.35%. Ordinal regression analysis of the six observed parameters, three parameters have a significant influence on SSR: shooting placement area (ASP), shooting placement distance (DSP), and the presence of frontal and nuchal eminence (FE, NE). The ASP at the point of the cross line between two lines from the center of the dorsal eye to the center of the contralateral horn base, DSP at a low position (DSP<3 cm), and presence of FE gave a relatively low of SSR. Thus, it can be concluded that the SSR of the use of NPPSS in Indonesia is relatively low and is influenced by ASP, DSP, and the presence of FE and NE.